A degree of recognition across policing: embedding a degree apprenticeship encompassing work-based research. Issue 1 (15th July 2021) - Pepper, Ian; Brown, Ian; Stubbs, Paul
Abstract : Purpose: As the police service across England and Wales moves towards degree-level study for new recruits as a component of recognising the profession of policing, this paper describes and discusses the introduction of the Police Constable Degree Apprenticeship (PCDA) and the core skills of evidence-based policing (EBP) as an educational theme for solving work-based problems. Design/methodology/approach: Authored by both policing practitioners and researchers, this paper refers to key literature whilst exploring the implementation of the PCDA as a component of a Policing Education Qualifications Framework (PEQF). It highlights some of the challenges faced with its implementation along with the benefits of the adopting this degree-level education and work-based programme where EBP is embedded in to both study and professional practice. Findings: There are significant benefits to the police service of adopting the PCDA as one of the entry routes for new police constables and embracing the educational development and professional application of EBP. However, this does not come without a number of challenges for the service and the professional body for policing. Originality/value: This paper, co-authored by both policing practitioners and researchers, provides a contemporary view on the introduction of the PCDA as an initial entry route for new police constables and the embedding of EBP within both their learning and professional practice. As the first graduates complete their studies, the paper discusses the opportunities the adoption presents and the challenges it faces both locally and nationally.